The Role of the Ismuhu Yahya Mosque in Helping the Government for the Welfare of the Community Through the “Pasar Bahagia” Program - Riwayati, Anny; Juminta, Juminta; Rizki, Abang Dede Predi; Rahmaniah, Syarifah Ema; Herlan, Herlan (Universitas Negeri Makassar, 2023)
The economic system adopted by Indonesia based on Pancasila and the 1945 Constitution has the implied meaning of placing the people in a noble position. An economy that always prioritizes the people with the principles of social justice or a just and prosperous society. An idea emerged from the community, namely in the Ismuhu Yahya Mosque area to move the Indonesian economy by launching the